Association between statin use and consultation or surgery for osteoarthritis of the hip or knee: a pooled analysis of four cohort studies. Issue 11 (November 2017) - Michaëlsson, K.; Lohmander, L.S.; Turkiewicz, A.; Wolk, A.; Nilsson, P.; Englund, M.
Summary: Objective: Experimental findings and previous observational data have suggested lower risk of osteoarthritis (OA) with statin use but results are inconsistent. Large-scale studies with a clinically important outcome are needed. Thus, we aimed to determine whether statin use is associated with a reduced risk of developing clinically-defined hip or knee OA. Design: Pooled analysis based on time-to-event analysis of four population-based large cohorts, encompassing in total 132, 607 persons aged 57–91 years resident in southern and central Sweden. We studied the association between statin use and time to consultation or surgery for OA of the hip or knee by time-dependent exposure analysis and Cox regression. Results: During 7.5 years of follow-up, we identified 7468 out- or inpatient treated cases of hip or knee OA. Compared with never use, current use of statins conferred no overall reduction in the risk of OA with an adjusted pooled hazard ratio (HR) of 1.04 (95% confidence intervals [95% CI] 0.99–1.10). We found no dose–response relation between duration of current statin use and the risk of OA, with similar HRs among patients with less than 1 year of use (HR 1.09; 95% CI 0.92–1.32) as in patients with use for 3 years or more (HR 1.05; 0.93–1.16). Results were comparable in those with low, medium and high dose of current statin use, without indications of heterogeneity of study results. Conclusion: Statin use is not associated with reduced risk of consultation or surgery for OA of the hip or knee.